Editorial Board - Journal, JCGC (Journal of Cultural Guidance and Counseling, 2025)
This journal focuses on presenting research on the integration of guidance and counseling science and educational psychology with cultural values ​​from various regions and countries both through traditional approaches such as books, guide modules, and through internet-based technology approaches such as web-based applications, Artificial Intelligence (AI), and Android-based applications that are following the times.